Drying and Solid-Liquid Extraction of Hydroxychavicol and Eugenol from Betel Leaves (Piper Betle L.) - Pin, Kar Yong (2009)
Betel (Piper betle L.) is one of the invaluable medicinal plants originated from Malaysia. Its leaves have been used traditionally for various medication purposes. Scientific research on the leaf of this plant reveals that it possesses many beneficial bioactivities and its extract from betel leaves has a great potential to be used in developing commercial products. However, there is a lack of research on the processing aspects to produce its bioactive extract. This research studied three key processes including drying, solid-liquid extraction, and freeze drying which are involved in processing of bioactive extract from betel leaves. Different experiments were designed and carried out to look into the effects of various operating parameters on the qualitative and quantitative aspects of betel leaves extract. Hydroxychavicol (HC) and eugenol (EU) were selected as the quality indicators of the product because these two compounds were reported to play an important role in the bioactivities of betel leaves including antioxidant, antiinflammatory, and anticarcinogenic and antibacterial. The effect of drying temperature on the quality of betel leaves and drying kinetics were studied in order to determine the optimum drying temperature. Changes in the concentration of HC and EU reveal that the optimum temperature for drying of betel leaves was 70oC because degradation of HC and EU was observed above this temperature. Logarithmic model was found to be the most suitable model among the selected thin layer models in predicting the process. Water was the most suitable solvent for extracting betel leaves compared to ethanol, ethyl acetate, and hexane. This was because it gave highest yield and the extract from water indicated high antioxidant and anti-inflammatory activities in which the activities were related to HC and EU. The optimum extraction temperature was determined as 60oC to avoid degradation of EU. The ratio of water to solid of 30:1 (ml:g) was found to be optimum based on analysis of Response Surface Methodology (RSM). Extraction kinetics of betel leaves reveals that the optimum extraction time is one hour. A new model named equilibrium driven solid-liquid extraction (EDSLE) model was developed and successfully applied in describing the process. The study of freeze drying process of betel leaves extract was conducted in two sections namely freezing and drying. The freezing kinetics data shows that the freezing point of betel leaves extract with 20%SC was about -4oC. Prediction of freezing kinetics and freezing time was carried out successfully with numerical model. The results of drying kinetics of betel leaves extract show that the increase of drying temperature increased the drying rate. Midilli et la. model was found to be the most effective one among the selected models for modeling of the process.